Characterization of light foamed concrete containing fly ash and desulfurization gypsum for wall insulation prepared with vacuum foaming process. (26th April 2021) - Gao, Hongyu; Wang, Weiguang; Liao, Hongqiang; Cheng, Fangqin
Graphical abstract: Highlights: The initial size of pores mainly was <1 mm and 2–3 mm under atmospheric condition. The vacuum foaming improvs foaming expansion ratio and properties of concrete. The total number of pores was the main impact factor on properties of concrete. The number of <1 mm pore was the main impact factor on the total number of pores. There was no correlation on properties of concrete with the number of 2–3 mm pore. Abstract: We studied lightweight vacuum-foamed concrete containing fly ash and desulfurisation gypsum by revealing the influence of experimental parameters on the foaming expansion ratio under vacuum and atmospheric conditions and the influence of vacuum degree on the properties of foamed concrete. The correlation between the porosity distribution and concrete block characteristics under vacuum was discussed. Vacuum foaming increased the foam expansion ratio and improved the properties of the foamed concrete. The increased vacuum degree increased the pore size. The number of <1-mm pores and the total number of pores were effective on the properties of foamed concrete.